EDUCATIONAL SPECIAL NEEDS PSYCHOLOGY - Angelika Amanda Oktaviana; Depi Triani, Lydia, Paulina Gresia, Ryan Fernando, Reynhard Malau (CV. ADIBA AISHA AMIRA, 2023)
This article discusses educational psychology for children wiyh special needs. This article reviews how to deal with children with special needs. How to teach it and make an approach to children with special needs. The results of this discussion are that educational psychology is a branch of psychology that specializes in how to understand tecahing and learning in the world of education.